THE ROLE OF ZAKAT IN REALIZING SUSTAINABLE DEVELOPMENT GOALS (SDGs) TO INCREASE COMMUNITY ECONOMIC INCOME - Anisa, Yulia; Mukhsin, Moh. (Al-Infaq: Jurnal Ekonomi Islam, 2022)
This study confirms the role of Zakat, Infak and Alms in achieving sustainable development goals in Indonesia. The Goals of Sustainable Development are goals jointly agreed by the member states of the United Nations (UN) with the aim of bringing prosperity and a decent life to all citizens. Of course, this is consistent with the purpose of zakat in Islam as a means of distributing funds from those who have too much wealth to those who have little wealth. Therefore, the purpose of this study is to see how much role zakat, infoac and almsgiving play in helping Indonesia achieve its SDG goals. Based on the results of the analysis carried out, it is clear that Zakat, Infak and charities actively participate in the five pillars of the program to achieve its sustainability goals in Indonesia. Economy, Health, Education, Da'wah, Social Humanity. Zakat, Infaq and Alms play a key role in financing the eight goals of Zakat recipients. (1) fakir, (2) miskin, (3) amil, (4) muallaf, (5) hamba sahaya, (6) Gharimin, (7) fii sabilillah, (8) ibn sabil. Play the biggest role in achieving the Sustainable Development Goals: Poverty, hunger, good health and quality education.